Associations between post-traumatic stress symptoms and quality of life among psychiatric healthcare personnel in China during the COVID-19 pandemic: A network approach - Zhao, Yan-Jie; Zhang, Cheng; Guo, Tong; Sha, Sha; Su, Zhaohui; Cheung, Teris; Jackson, Todd; An, Feng-Rong; Xiang, Yu-Tao (Frontiers in Psychiatry, 2023)
Background: Post-traumatic stress symptoms (PTSS) are commonly reported by psychiatric clinicians during the coronavirus disease 2019 (COVID-19) pandemic and negatively affect quality of life (QOL). However, associations between PTSS and QOL at symptom level are not clear. This study examined the network structure of PTSS and its connection with QOL in psychiatric clinicians during the COVID-19 pandemic. Methods: This cross-sectional study was carried out between March 15 and March 20, 2020. The 17-item Post-Traumatic Stress Disorder Checklist – Civilian version (PCL-C) and World Health Organization Quality of Life Questionnaire - Brief Version (WHOQOL-BREF) were used to measure PTSS and global QOL, respectively. Network analysis was used to investigate the central symptoms of PTSS and pattern of connections between PTSS and QOL. An undirected network was constructed using an extended Bayesian Information Criterion (EBIC) model, while a directed network was established based on the Triangulated Maximally Filtered Graph (TMFG) method. Results: Altogether, 10,516 psychiatric clinicians completed the assessment. “Avoidance of thoughts” (PTSS-6), “Avoidance of reminders” (PTSS-7), and “emotionally numb” (PTSS-11) were the most central symptoms in the PTSS community, all of which were in the Avoidance and Numbing domain. Key bridge symptoms connecting PTSS and QOL were “Sleep disturbances” (PTSS-13), “Irritability” (PTSS-14) and “Difficulty concentrating” (PTSS-15), all of which were within the Hyperarousal domain. Conclusions: In this sample, the most prominent PTSS symptoms reflected avoidance while symptoms of hyper-arousal had the strongest links with QOL. As such, these symptom clusters are potentially useful targets for interventions to improve PTSS and QOL among clinicians at work under pandemic conditions.